Histomorphological and clinicopathological correlates of reflux esophagitis - V., Vidhya; Joseph, Leena Dennis; P., Ganesh; Jeswanth, Jesse (International Journal of Research in Medical Sciences, 2021)
Background: Inflammatory lesions of the esophagus are major concerns to patients who visit our Medical Out Patient Department (OPD) on a regular basis. Endoscopic examination, with histopathological confirmation is the diagnostic modality employed in many centers. Endoscopic appearance is characteristic, and so are histomorphological findings. In our study we have analyzed the clinical, endoscopic and histomorphological findings of various types of esophagitis. This will help us to arrive at a correct diagnosis to initiate appropriate therapy. Methods: We included 141 cases of esophagitis reported in Sri Ramachandra Institute of Higher Education and Research from January 2016 to December 2020 in our study, mostly the ones which came as biopsy samples in histopathology section. Slides were reviewed, various histological features, clinical and endoscopic findings were correlated. Microsoft excel was used for the calculation of results. Results: Reflux esophagitis was most commonly seen in male patients (64%), between 40-60 years (35%) of age with presenting complaints of heart burn and clinical diagnosis of reflux esophagitis. Classic histological feature for the diagnosis of reflux esophagitis was epithelial hyperplasia noted in 89% male and 86% female patients, followed by increased basal cell thickness noted in 66% male and 55% female patients. Conclusions: Accurate diagnosis of reflux esophagitis is mainly based on histomorphological features. Capillaries in epithelium and basal cell hyperplasia along with history and endoscopic appearance to be considered for the diagnosis of reflux esophagitis.